Enhancing Students’ Scientific Literacy using Virtual Lab Activity with Inquiry-Based Learning - Liandha Arieska Putri; Anna Permanasari; Nanang Winarno; Nur Jahan Ahmad (Journal of Science Learning, 2021)
Laboratory activity is closely related and yet is essential in the process of science teaching-learning. The hands-on laboratory experiment is the one normally used in school. Particularly with the state of online schooling, it is quite challenging to perform a hands-on laboratory activity. The combination of inquiry-based learning with virtual lab activity can be an alternative to developing a more alluring yet meaningful learning process within online learning. This research aims to analyze virtual lab activity with inquiry-based learning on students’ scientific literacy in light and optics topics. Participants were taken from junior high school students in the 8th-grade in Bandung, Indonesia. It includes 40 students with 14 males and 26 females with ages range 13-14 years old who have not yet studied light and optics. A pre-experimental research method with a one-group pre- the post-test design was used. The finding indicates that students’ scientific literacy was significantly increased with a medium category (N-Gain score 0.441). Based on this research, virtual-lab activity with inquiry-based learning could be considered an alternative to conducting a meaningful online learning activity, especially in science education.